FEMININE TRANSGRESS: SOCCER. A LOOK FROM THE PRESS CARTOON, MEXICO 1970-1971 (Tzintzun, Revista de Estudios Históricos, 2016)
The main interest of this research paper is to analyze through the cartoon andsome press news the construction of the speech that was done by “Excelsior” and“El Día” related to women and their irruption in the first women internationalchampionships done in Italy (1970) and Mexico (1971). We took the idea thatfootball became a conflict area for Mexican people that desired to practice thissport since they were generally defined as transgressors to the conditions andsocial values that should define them, and we ask about the role of the press in theelaboration of this vision. In this sense, we are specially interested in study theperspectives of the gender that press expressed, reproduced and projected aroundwomen, football and players from a triple connotation: as expression of sharedideas by the universe of their readers, as a diffusion channel of the speech of thedominating gender, and as a producer of imaginary collectives that finished updefining a particular perception of this sport and the appropriation by women ofa reserved land, at least symbolically, to the expression of masculinity.
Keywords: Press; cartoon; football; women; gender